Faktor- Faktor Yang Berhubungan Dengan Kepatuhan Penggunaan Alat Pelindung Diri (APD) Pada Perawat Rawat Inap di Rumah Sakit X Tahun 2024: Kepatuhan Penggunaan Alat Pelindung Diri (APD) - Nuraeni; Cempaka, Eka; Handayani, Putri; Utami, Desyawati (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
The purpose of this study was to determine the factors related to compliance with the use of personal protective equipment (PPE) in inpatient nurses at hospital X in 2024. This type of research is quantitative using a cross-sectional study design. The population of this study included all inpatient nurses at hospital X, totaling 214 nurses. This study uses primary data from observation results, namely compliance with the use of personal protective equipment (PPE) including knowledge, attitudes, rewards and punishments, and length of service with a questionnaire. While secondary data is internal company data in the form of a general description of the company, number of workers, Standard Operating Procedures (SOP), and data from the K3RS/PPI team at hospital X. The data analysis technique for this study is univariate data analysis and bivariate data analysis. The results showed that the highest proportion of compliance variables were nurses who were compliant and not compliant, the highest proportion of knowledge was nurses who were knowledgeable, the highest proportion of attitudes was nurses who behaved well, the highest proportion of rewards and punishments was walking, the highest proportion of length of service was nurses with a risky length of service. There is no relationship between knowledge and compliance with the use of personal protective equipment (PPE), there is no relationship between attitudes and compliance with the use of personal protective equipment (PPE), there is no relationship between reward and punishment and compliance with the use of personal protective equipment (PPE), there is no relationship between length of service and compliance with the use of personal protective equipment (PPE).